Detection of antimicrobial resistance by means of phenotypic and genotypic tests in Staphylococcus aureus recovered from central vascular catheters - Faria, Rafael César Bolleli; Silveira, Luciano Alves Matias; D'Amorim, Mariana Figueiredo Guedes; Moreira Neto, João Felipe; Barbosa, Boscolli Pereira; Vieira, Carlos Ueira; Terra, Ana Paula Sarreta; Bonetti, Ana Maria (Revista de Ciências Médicas e Biológicas, 2012)
<!--[if gte mso 9]> 800x600 <![endif][if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->Staphylococcus aureus resistant to multiple antibiotics represent an important problem in nosocomial infection control. The profile of antimicrobials resistance of S. aureus isolated from central vascular catheters from Intensive Care Unit (ICU) patients (Triangulo Mineiro University College Hospital). The S. aureus were evaluated by antimicrobial tests, detection of the mecA gene and RAPD (Random Amplified Polymorphic DNA), of the resistance to penicillin (94,7%) and ampicillin (86,8%) was high. One isolate presented resistance to vancomyci. The association of results obtained by phenotypic test with the presence of the mecA gene was evaluated. Out of 49 S. aureus evaluates, 23 (47%) presented resistance to oxacilin, and it is possible to detect the presence of the resistance mecA gene in 21 (43%). The by RAPD patterns allowed established into two different phenotypic groups, the ones that presented resistance and the ones susceptible to antimicrobial substances, with a dissimilarity of 73,3%. Molecular markers for detection of resistance to oxacilin, as the mecA gene, were found to be more sensitive than the phenotypic markers.